2002
DOI: 10.1021/la011435i
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes in SDS Micelles Induced by Hydrotropic Salt

Abstract: The addition of low concentrations of the hydrotropic salt p-toluidine hydrochloride (PTHC) to solutions of the anionic surfactant sodium dodecyl sulfate (SDS) promotes the transition from spherical to rodlike micelles. NMR measurements confirm that the hydrotrope adsorbs at the micelle-water interface, thereby screening electrostatic repulsions between the surfactant headgroups. The sphere-to-rod transition in dilute solutions is followed using quasielastic light scattering, and in the semidilute concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
243
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(261 citation statements)
references
References 40 publications
17
243
1
Order By: Relevance
“…At equilibrium, the organic counter-ion PTHC has the tendency to remain at the micelle-water interface, decreasing the spontaneous curvature of the micellar aggregates and transforming them from cylinders to bilayers (13,14). The equilibrium phase behavior of the concentrated phases was investigated recently in this system, and a novel isotropic phase ðL i Þ of bilayers was reported (15).…”
mentioning
confidence: 95%
“…At equilibrium, the organic counter-ion PTHC has the tendency to remain at the micelle-water interface, decreasing the spontaneous curvature of the micellar aggregates and transforming them from cylinders to bilayers (13,14). The equilibrium phase behavior of the concentrated phases was investigated recently in this system, and a novel isotropic phase ðL i Þ of bilayers was reported (15).…”
mentioning
confidence: 95%
“…Recently, one of us was involved in a study where we identified p-toluidine hydrochloride (PTHC) as a binding salt that could rapidly induce the growth of SDS worms. 6 One issue with using SDS to form wormlike micelles is that the zero-shear viscosity of these solutions is typically quite low (∼1 Pa‚s). This is probably related to the short (C 12 ) tail length of SDS, whereas, in comparison, popular worm-forming cationic surfactants (e.g., cetyl trimethylammonium bromide, CTAB) have 16 carbons or more in their tails.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrotrope partitions into the surfactant headgroup region and results in dramatic micellar growth. Similarly, a cationic hydrotrope can drive the growth of anionic micelles [5]. As the molecular weight (or length) of the hydrophobic portion of the hydrotrope is increased, the hydrotrope begins to behave more like a second surfactant and can alter the self-assembly in solution, leading to the formation of vesicles.…”
Section: Introductionmentioning
confidence: 99%